Langerhans cell histiocytosis in cervical node in an adult female - a case report (Medical Journal of Indonesia, 2013)
A case of Langerhans Cell Histiocytosis (LCH) in a 58 year old woman who presented with bilateral cervical adenopathy without any other complaints is reported. Clinical examination did not reveal any other positive finding except the adenopathy. Histopathological examination confirmed the node to be Langerhans cell histiocytosis. In conclusion, LCH is a rare disease with varied clinical presentation, including cervical adenopathy. Diagnosis should be confirmed by histopathological examination of biopsy specimen. Observation may be an effective management strategy in cases of adult LCH with cervical adenopathy as the only symptom, due to its possible spontaneous regression. (Med J Indones. 2013;22:114-6)